Efficacy and safety of DL‐3‐N‐butylphthalide in the treatment of ischemic poststroke aphasia: A randomized clinical trial - Jing Tian; Peng Yang; Jianing Yang; Rui Wang; Biyi Zhou; Kun Zhang; Yanying Zhao; Binbin Wang; Lijuan Liu; Ruomeng Chen; Haoran Wu; Ruihan Miao; et al. (Annals of Clinical and Translational Neurology)
Abstract Objective Poststroke aphasia (PSA) has a high prevalence and requires a long recovery period, severely impairing life and work. Its existing behavioral interventions, principally speech and language therapy, are limited by numerous factors. The aims of this study are to evaluate the efficacy and safety of DL‐3‐N‐butylphthalein (NBP) and explore its mechanism in the treatment of ischemic PSA. Methods Patients hospitalized in the Second Hospital of Hebei Medical University in China were randomly administered NBP soft capsules or placebo orally for 6 months from July 1, 2021, to February 25, 2023. Language skills were assessed using the Western Aphasia Battery‐Aphasia Quotient (WAB‐AQ). We collected plasma samples and detected neurotransmitters by liquid chromatography‐mass spectrometry. Results In total, 118 out of 124 patients were included in the outcome analysis. Compared with the control group, AQ values in the NBP group significantly improved at 6 months (U = 1187.5, p = 0.003). After eliminating baseline interference, NBP treatment was independently associated with the 6‐month AQ improvement [mean difference (MD) 0.106, 95% confidence interval (CI) 0.018, 0.195, p = 0.019]. We observed no statistically significant difference between the groups in abnormal liver function at 1 month [relative risk (RR) 1.07, 95% CI 0.89, 1.28] and 6 months [RR 0.99, 95% CI 0.86, 1.42]. Statistically significant differences were observed in tyrosine (p = 0.043) and 5‐hydroxytryptophan (p = 0.041) between the two groups. Interpretation NBP treatment might promote the recovery of WAB‐AQ in patients with ischemic PSA by increasing levels of monoamine neurotransmitters.